Social Capital, Accountability, and Rural Waqf Governance: A Proposed Model for Sustainable Community-Based Waqf Management - Sitti Mukarramah; Iqbal M. Aris Ali; Basirun Ningsih; Rosita Alting; Akhmad Roja Badrus Zaman (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2026)
This study examines rural waqf governance developed through informal mechanisms grounded in trust, social capital, and community-based practices in Woka Jaya Village, East Halmahera. The study aims to formulate an integrated rural waqf governance model that explains how spiritual values, local social relations, asset utilization, and accountability practices interact in sustaining waqf management. Using an interpretive qualitative case study, the research involved eight purposively selected informants representing waqif, nazhir, beneficiaries, and the village government. Data were collected through in-depth interviews, participant observation, and document review, then analyzed thematically through data reduction, theme coding, data presentation, and interpretive conclusion drawing, supported by source and method triangulation. The findings show that waqf governance is shaped by the values of trustworthiness, worship, mutual cooperation, deliberation, and confidence in religious leaders. Waqf assets are utilized in the form of land for religious and educational facilities, coconut plantation benefits for social and religious financing, and community labor for collective activities. Downward accountability is practiced through oral transparency, direct communication, community forums, and deliberative decision-making, although legal formalization, documentation, financial recording, and administrative continuity remain limited. The study proposes a Social Capital-Based Integrated Rural Waqf Governance Model comprising six dimensions: spiritual values, social capital, nazhir legitimacy, transformation of local assets, downward accountability, and modern institutional reinforcement. The study contributes theoretically by positioning social capital as a governance mechanism and contributes practically by emphasizing the need to integrate local values with asset legalization, documentation, transparent reporting, nazhir professionalization, and gradual digital accounting for sustainable rural waqf management.